The Effect of Ginger (Zingiber officinale) Extract Addition on The Characteristics of Chayote (Sechium edule (Jacq.) Sw.) Syrup - Amelia, Kharisma; Sylvi, Diana; Sayuti, Kesuma (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2025)
This study aimed to evaluate the effect of adding ginger (Zingiber officinale) extract on the physical, chemical, microbiological, and sensory properties of chayote (Sechium edule) syrup, a potential functional drink developed from local agricultural produce. The research was designed using a Completely Randomized Design (CRD) with five levels of ginger extract addition (0%, 10%, 20%, 30%, and 40%) and three replications. Data were analyzed using Analysis of Variance (ANOVA), and Duncan’s New Multiple Range Test (DNMRT) at a 5% significance level was applied when significant differences were detected. The results showed that increasing the concentration of ginger extract significantly improved syrup viscosity (up to 1568.67 cP), phenol content (up to 45.65 mg GAE/g), and antioxidant activity (up to 46.03%), while reducing TPC to 2.7×10² CFU/g. The most preferred formulation was at 30% ginger extract addition, yielding a product with desirable sensory qualities and balanced composition. Color analysis using °Hue showed a shift towards deeper yellow tones, although this was not statistically significant. High viscosity contributes to better texture and product stability, while elevated phenol and antioxidant content enhance the health-promoting potential of the syrup. These attributes are essential in designing functional beverages.